PTU-037 Loss of TLR 2 and 4 on ileal plasmacytoid dendritic cells in post-operative Crohn's disease patients. (23rd September 2015) - Murugananthan, A U; Bernardo, D O; Tee, C T; Arebi, N; Knight, S C; Al-Hassi, H O
Abstract : Introduction: Aberrant responses to bacterial flora are implicated in post-operative recurrence of Crohn's disease (CD) after ileo-ceacal resection. Response to gut flora is conducted by dendritic cells (DC) which can induce a tolerogenic or active immune response. DC express Toll like receptors (TLR) which recognise bacterial products and are important in immune tolerance in health and highly expressed in IBD colonic tissue. Two subsets of DC are plasmacytoid (PDC) and myeloid cells (MDC). These DC show functional differences in their response to bacteria and are able to cross-talk. Expression of TLR on DC in the small intestine of post-operative CD patients is still largely unknown. We aimed to assess expression of TLR on DC from lamina propria mononuclear cells (LPMC) in post-operative CD patients as compared with normal controls. Methods: Small intestine biopsies were obtained from 18 post-operative CD patients and 5 controls by colonoscopy. LPMC were collected using collagenase digestion, labelled with monoclonal antibodies to TLR2 and 4 and assessed by multicolour flow cytometry. Result: A high percentage of DC from normal ileum expressed TLR2 and 4 with no significant differences in expression between PDC and MDC. However, expression of TLR 2 and 4 was significantly lower in PDC from post op CD patients compared with PDC in normal controls (mean 22.30% vs 60%, p=0.0003 and 38.55% vs 65.16%, p=0.02), respectively. Furthermore, PDC and MDC differed in expression of TLR2 and 4 in tissues from post-op CD patients; PDC expressed significantly less TLR2 and 4 compared with MDC (22.30% vs 38.11%, p=0.002 and 38.55% vs 50.89%, p=0.01), respectively. Conclusion: Reduction of TLR2 and 4 expression in PDC compared with their counterparts in normal controls is likely to be the reason for the reduced expression of both TLRs on PDC compared with MDC in CD tissues. The lack of TLR2 and 4 expression on PDC maybe related to the disease activity as the normal controls did not show any statistical differences in expression of either TLR between the DC subsets. Other groups have suggested that functional differences exist between PDC and MDC in their activation by bacterial products and ability to produce innate and acquired inflammatory responses. In particular, blood PDC require the presence of MDC to respond to bacterial products to activate T cells rather than driving innate immunity. Our results indicate that PDC response to intestinal microflora may differ from that in MDC and provide initial background to the DC function and diversity in post-operative CD recurrence.